Forecasting Exchange Rate Across Countries with Gold Price as Exogenous Variable Using Transfer Function and VARI-X Model (MATEMATIKA, 2020)
Investors and collectors hold gold as protection for their savings and wealth atlarge. Gold does not pay interest like treasure bonds or savings accounts, but current goldprices often reflect increases and decreases of an asset. This research aims to provide amodel for the relationship between the exchange rate, which is vital in exporting gold, andgold prices across countries. The Australia, Brazil, and South Africa exchange rates areused as a case study against the gold price. The ARIMA model is used for forecasting goldprice as an input for the Transfer Function and VARIX models. The Transfer Functionmodel only considers the relationship between gold prices as input with the exchange ratein each country, whereas the VARIX model also considers the interrelationship betweenexchange rates in these countries. Daily data is used for the period 1st June 2010 to the28th February 2018. The RMSE and MAPE are used as criteria for selecting the bestmodel. The results show that VARIX is the best model for forecasting the Australianexchange rate, while the Transfer function is the best model for forecasting South Africanand Brazilian exchange rates.